Efeito do recurso audiovisual no nível de ansiedade e na aquisição de conhecimento em pacientes em pré-operatório de revascularização do miocárdio: ensaio clínico randomizado - Araújo, Naryllenne Maciel de (2022)
In the period before coronary artery bypass graft surgery, lack of knowledge and feelings such as anxiety can be a cause of risks in the perioperative period. Thus, the use of audiovisual resources in nursing is capable of providing assistance, contributing to health education and increasing patient confidence. The present study aims to evaluate the effect of the audiovisual resource on the acquisition of knowledge about the level of anxiety in the preoperative period of myocardial revascularization. This is a randomized controlled clinical trial, carried out in the cardiology ward of Hospital Rio Grande, during the year 2021. The sample consisted of 44 patients in the preoperative period of myocardial revascularization surgery, equally divided into a Control Group (CG ), which received verbal preoperative nursing guidance as an intervention, and the Experimental Group (EG), which received the same verbal preoperative guidance, plus the application of an explanatory video about the surgery as an audiovisual resource. Randomization was performed through the website www.randomizer.org to choose by simple randomization of patients in both groups. Thus, after allocation to groups for data collection, at first, a researcher applied the instrument to assess anxiety in all participants before the interventions; in the second moment, the main researcher carried out the interventions in both groups; and, finally, the first researcher, not knowing which participant belonged to which group, applied the anxiety instrument and an instrument to assess the knowledge acquired in the two post-intervention groups. These instruments for data collection are an instrument to assess the level of anxiety, the State-Traced Anxiety Inventory – STAI, and an instrument that assesses knowledge about surgery. Data were analyzed using descriptive and inferential statistics, arranged in tables and charts presented in the results of this research. The present study was approved by the Research Ethics Committee, CAAE nº 40743520.9.0000.5537, Opinion 4,579,278. And it was registered on the Brazilian Clinical Trials Registry (RBR- 24c5qwm) virtual platform. Most patients were male, elderly, and with incomplete or complete elementary education. After the interventions in both groups, it was possible to prove the increase in the feeling of preparation and confidence to perform the surgery, whereas the experimental group obtained a greater report of confidence after the intervention. Regarding the level of knowledge, there was an increase in acquisition in both groups (p<0.05), with the group that used the audiovisual resource getting better results, with an average response of 7.77 and the highest number of correct answers in the questions about preoperative, intraoperative and immediate postoperative care. Regarding the level of anxiety, it also decreased in both groups, with more expressive values in the experimental group (p<0.05), decreased both the STAI-State values and the STAI-Trace after interventions. In addition, the experimental group also obtained a 100% decrease in moderate levels of anxiety in the STAI-State, also presented a decrease in negative feelings such as tension and worry, and an increase in positive feelings in the preoperative period. No participant had a high level of anxiety during the research. It is concluded that the effect of the video during nursing guidelines as health education is positive and improves anxiety levels, proving its effectiveness and thus confirming the alternative hypothesis of this study. In addition, it allows a better patient experience during the preoperative period, increasing their knowledge, in addition to helping the Nursing Process with a technological tool applied to health.